Characterization of an epoxide‐derived metabolite of dictamnine using high‐performance liquid chromatography with hybrid linear trap quadrupole orbitrap mass spectrometry. Issue 24 (25th November 2016) - Feng, Pinning; Hu, Xinrong; Wu, Xiaoliang; Dong, Jun; Cai, Xiuyu
Abstract : Dictamnine (4‐methoxyfuro[2, 3‐b]quinolone), a furoquinoline alkaloid of the Rutaceae plant family, has been reported to be a phototoxic and photomutagenic compound, whose exposure can cause carcinogenicity, cytotoxicity, and genotoxicity. Metabolic activation is suggested to play an important role in dictamnine‐induced toxicities, and the epoxide metabolite of dictamnine has been reported to be the main intermediate in vitro. The objective of this study was to identify N ‐acetylcysteine conjugate(s) derived from this reactive dictamnine metabolite in vitro and in vivo. An N ‐acetylcysteine conjugate of dictamnine was detected in microsomal incubations of dictamnine, as well as bile and urine samples of rats treated with dictamnine. The data obtained from the present work will facilitate the understanding of the mechanism behind dictamnine‐induced toxicities.